2017
DOI: 10.1210/jc.2017-02255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Response to Therapy and Mortality in Patients With Thyroid Cancer at High Risk of Recurrence

Abstract: Age was a key predictor of response to therapy and disease-specific survival in ATA high-risk thyroid cancer patients. Its incorporation as a variable in the ATA risk stratification system would improve its power to predict response to therapy as well as mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 34 publications
4
44
1
Order By: Relevance
“…Younger age was identified to be associated with aggressiveness of PTC, such as vascular invasion and lymph node metastases (26). However, there is mounting evidence that younger PTC patients have a better disease-specific survival although they present high-risk clinical-pathological features (27)(28)(29). For PTMC under active surveillance, younger age was also associated with more probability of disease progression like tumor enlargement by ≥3 mm or novel appearance of nodal metastasis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Younger age was identified to be associated with aggressiveness of PTC, such as vascular invasion and lymph node metastases (26). However, there is mounting evidence that younger PTC patients have a better disease-specific survival although they present high-risk clinical-pathological features (27)(28)(29). For PTMC under active surveillance, younger age was also associated with more probability of disease progression like tumor enlargement by ≥3 mm or novel appearance of nodal metastasis (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, a tendency toward a lower frequency of structural incomplete response was observed at the end of follow-up in patients with intermediate and high RR less than 40 years, without statistical significance. Indeed, other authors demonstrated that age was a key predictor for the response to therapy in patients with high RR (Shah et al 2018). Moreover, high-risk younger patients with a structural incomplete response to therapy had a significantly better disease specific survival (DSS) than older patients (74 vs 12%, respectively, P < 0.001) (Shah et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, other authors demonstrated that age was a key predictor for the response to therapy in patients with high RR (Shah et al 2018). Moreover, high-risk younger patients with a structural incomplete response to therapy had a significantly better disease specific survival (DSS) than older patients (74 vs 12%, respectively, P < 0.001) (Shah et al 2018). The RR classification system was also validated in patients with low and intermediate risk or recurrence who did not receive RA.…”
Section: Introductionmentioning
confidence: 99%
“…For papillary carcinoma, the presence of distant metastases in elderly patients as well as carcinomas with tumor size above 3 cm requiring aggressive intervention in younger ones are recognized to be important prognostic factors [9]. According to some other information, only distant metastases into bones belong to negative prognostic factors [26], the patient's age is thought to be an important prediction factor only for drug response prognosis [27].…”
Section: Groupsmentioning
confidence: 99%